Combined application of neuromuscular electrical stimulation and voluntary muscular contractions. Review article - Paillard, T. (Sports Medicine, 2008)
Electromyostimulation (EMS) and voluntary muscle contraction (VC) constitute different modes of muscle activation and induce different acute physiological effects on the neuromuscular system. Long-term application of each mode of muscle activation can produce different muscle adaptations. It seems theoretically possible to completely or partially cumulate the muscle adaptations induced by each mode of muscle activation applied separately. This work consisted of examining the literature concerning the muscle adaptations induced by long-term application of the combined technique (CT) [i.e. EMS is combined with VC - non-simultaneously] compared with VC and/or EMS alone in healthy subjects and/or athletes and in post-operative knee-injured subjects. In general, CT induced greater muscular adaptations than VC whether in sports training or rehabilitation. This efficiency would be due to the fact that CT can facilitate cumulative effects of training completely or partially induced by VC and EMS practiced alone. CT also provides a greater improvement of the performance of complex dynamic movements than VC. However, EMS cannot improve coordination between different agonistic and antagonistic muscles and thus does not facilitate learning the specific coordination of complex movements. Hence, EMS should be combined with specific sport training to generate neuromuscular adaptations, but also allow the adjustment of motor control during a voluntary movement. Likewise, in a therapeutic context, CT was particularly efficient to accelerate recovery of muscle contractility during a rehabilitation programme. Strength loss and atrophy inherent in a traumatism and/or a surgical operation would be more efficiently compensated with CT than with VC. Furthermore, CT also restored more functional abilities than VC. Finally, in a rehabilitation context, EMS is complementary to voluntary exercise because in the early phase of rehabilitation it elicits a strength increase, which is necessary to perform voluntary training during the later rehabilitation sessions.